Explaining ethnic disparities in bachelor's degree participation: Evidence from NZ - Lisa Meehan; Gail Pacheco; Zoe Pushon (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2017)
There are substantial ethnic gaps in higher education in NZ, despite more than a decade of considerable policy effort aimed at this concern. This study uses newly linked administrative data to examine the underachievement of Māori and Pasifika relative to Europeans. We follow a population cohort born between 1990 and 1994 from school through to young adulthood to assess the relative contributions of prior academic performance, socioeconomic status and parental education to these gaps. Controlling for the relevant covariates narrows the Māori-European gap, and eliminates the Pasifika- European gap in bachelor's degree participation rates. Utilising Fairlie decompositions, we find that school performance is by far the largest contributor to the ethnic gaps. Low socioeconomic status and parental education are also pertinent, but less important. Our results suggest that ethnic-based policies aimed at encouraging participation are likely to have a limited effect if used in isolation, and signal the need for policy interventions earlier in the education system.
Keywords: I21; I24; 330; Higher education; ethnicity; bachelor's degree; decomposition